Identification and Assessment of Human Errors Using SHERPA in the Endodontic Department of Clinic of Dentistry Faculty, Qazvin University of Medical Sciences - Mojtaba Jafarvand; Mojtaba Jafarvand; Samira Kazemi; Sakineh Varmazyar; Masumeh Ghorbanideh (پژوهش‌های سلامت‌محور, 2017)
Background & Objectives The Endodontic unit in dentistry occupation has a high sensitivity and any obvious or hidden human error can endanger the health of both the patient and the dentist.The aim of the present study was to identify and evaluate human errors using SHERPA technique in the Endodontic Department of Clinic of Dentistry Faculty in Qazvin University of Medical Sciences. Methods: This descriptive and cross-sectional study was conducted from 26/4/2017 to 21/8/2017. The number of error per task was obtained using worksheet of SHERPA including: task code, job task, error type, error description, error consequence and risk level. At first, using hierarchical task analysis, steps of doing work in the unit were divided into tasks and sub-tasks and nine critical tasks were determined. Then, using SHERPA technique, types of errors were identified and their risk was evaluated. Results: A total of 148 human errors were identified in the Endodontic Department of Clinic. The highest error rate was in the tasks of examination and history taking with 35 errors, and the lowest error rate was on the task of anesthetizing with 7 errors. Among all the main tasks, the most frequent errors were of functional type at the task of the treatment plan (9.45%). Also, 52.63% of errors were related to the functional errors with an undesirable risk level. Conclusion: The results of this study indicate that in order to reduce the occurrence of errors in the dentistry profession, it is necessary to take control measures such as using competent people, adjusting the number of patients with the number of specialists, balancing work hours and rest, and developing guidelines. Keywords: Endodontic, Human error, SHERPA technique, Dentistry Citation: Jafarvand M, Khoshnvaz H, Kazemi S, Varmazyar S, Ghorbanideh M. Identification and Assessment of Human Errors Using SHERPA in the Endodontic Department of Clinic of Dentistry Faculty, Qazvin University of Medical Sciences. Journal of Health Based Research 2017; 3(3): 267-276.